Democracy, Conflict and Development - Three Cases. - Stewart, F; Sullivan, M (QEH (University of Oxford), 1998)
This paper explores the connections between democracy, peace and development in three cases of recent history - Uganda, Kenya and Sri Lanka. It is shown that there are no simple and universal relationships. The experience of all three countries shows that democratic institutions are not sufficient to prevent conflict and can foment it in sharply divided societies. The case of Sri lanka suggests that redesigning democratic institutions in order to reduce conflict can fail to do so and may actually accentuate it. The paper concludes that inclusive government, politically and economically, is necessary to prevent conflict. This entails political participation by all major groups and a spread of economic benefits throughout society. Such inclusive government may be consistent with non-democratic structures and may often be undermined by democratic institutions, especially where violence is recent and threatening. Political and economic conditionality should aim to promote inclusive government and even development, even at the cost of conventional economic conditionality and the promotion of democracy, in violence-prone societies.